IMPACT OF FINANCIAL LITERACY ON INVESTORS: A SYSTEMATIC LITERATURE REVIEW USING PRISMA PROTOCOL - Maurya, Ritika; Mohta, Anu; Shunmugasundaram, V (International Journal of Accounting & Finance Review, 2023)
Financial literacy is the potential to understand and productively use different financial skills such as managing finance, budgeting and investing. FL has been considered one of the most important factors to improve the growth of investors and the economy as a whole. This study’s main purpose is to present a Systematic Literature Review (SLR) on FL and Investment between 2012 and 2021. The Systematic Literature Review analysis has been performed based on the PRISMA to analyse 26 related articles obtained from the Web of Science, Taylor and Francis and Jstor database. The review of the paper has been categorised based on publication year, a journal list, publication by authors number, features of review articles, tools and techniques applied, variables, findings and practical implications and outcomes of the area of study. The outcomes of this paper provide an understanding of the publication criteria of financial literacy and investment along with that it also offers possible approaches for further publications. The findings of the study also analyse the impact of financial literacy on investors. The study will provide an in-depth understanding of the concepts of Financial Literacy. The study suggests that future researchers initiate further research on financial literacy and investment and also diversify the broader study period. This paper is the first of its kind to identify the impact of investment preference on investors. JEL Classification Codes: G50, G51, G52, G53.